The mechanotransduction-immune axis in organ fibrosis: dual regulatory mechanisms and translational therapeutic perspectives - Lei, Chao; Wu, Dongjie; Zhang, Houyan; Yang, Zhiya; Huang, Bohao; Wang, Jie; Li, Yanbo; Lv, Wenliang (Frontiers in Immunology, 2025)
Organ fibrosis represents a final common pathway of chronic tissue injury, characterized by persistent extracellular matrix (ECM) accumulation and progressive loss of organ function. While canonical inflammatory and profibrotic cascades have been extensively studied, emerging evidence highlights the pivotal role of mechanotransduction-the process by which cells sense and transduce biomechanical cues-in orchestrating immune responses and driving fibrotic remodeling. This review conceptualizes the mechanotransduction-immune axis as a dual regulatory network wherein mechanical forces not only activate profibrotic signaling in resident stromal cells but also dynamically reprogram immune cell phenotypes and functions. We systematically delineate the molecular and cellular mechanisms by which matrix stiffness, shear stress, and mechanical stretch engage integrins, focal adhesion kinase, Piezo1, and TRPV4 to coordinate inflammatory signaling and ECM remodeling. Additionally, we discuss how immune cells, including macrophages, T cells, and neutrophils, sense and respond to mechanical inputs to amplify profibrotic responses. Finally, we summarize emerging translational therapeutic perspectives targeting this mechanotransduction-immune interplay, encompassing small-molecule inhibitors, nanomedicine approaches, gene editing technologies, and cell therapies. By integrating mechanistic insights and translational strategies, this review aims to provide a comprehensive framework for understanding and therapeutically targeting the mechanotransduction-immune axis in organ fibrosis.